2018
DOI: 10.14366/usg.17016
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic analysis of radiation-induced damage in common carotid arteries by using color Doppler ultrasonography

Abstract: PurposeThe aim of this study was to assess vascular changes and blood flow abnormalities in the common carotid arteries of patients with head and neck cancers after external radiotherapy, using color Doppler ultrasonography.MethodsWe studied 24 patients treated with external radiotherapy for various head and neck cancers. In order to study the acute effects of irradiation on common carotid blood flow and arterial diameter changes, color Doppler ultrasonography parameters such as peak systolic velocity, end dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Thus, future survivorship care plans should include stroke as a complication and its management. For example, carotid artery sonography should be performed regularly to detect the carotid artery stenosis , and early interventions such as antiplatelets or stent insertion could be applied, although the benefits are still undetermined .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, future survivorship care plans should include stroke as a complication and its management. For example, carotid artery sonography should be performed regularly to detect the carotid artery stenosis , and early interventions such as antiplatelets or stent insertion could be applied, although the benefits are still undetermined .…”
Section: Resultsmentioning
confidence: 99%
“…Radiation promoted the aging process in blood vessels and accelerated the risk of ischemic stroke in the OCC survivors after primary surgery. Therefore, secondary prevention should include stroke as a late complication for surveillance in cancer survivorship programs which may incorporate regular follow-up by carotid artery sonography and early interventions such as anti-coagulants or stent insertion [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms underlying stroke risk as a result of radiation exposure have been addressed in previous radiobiology studies. An increasing number of studies have indicated that post-irradiation damage to the arteries and heart is one of the most common undesirable effects of radiotherapy in cancer patients ( 22 ). These arterial changes may lead to late adverse effects of radiotherapy such as strokes or ischemic attacks ( 23 ).…”
Section: Discussionmentioning
confidence: 99%